Site engagement in implementation research: Introducing SEAMLIS as a conceptual and measurement framework - Sarah D. Jones; John P. Bartkowski; Steven Belenko; Jennifer E. Becan; Faye S. Taxman; Gail A. Wasserman; Gregory A. Aarons; Larkin S. McReynolds; Cheyenne Dolbear; Xiaohe Xu (Health & Justice)
Abstract Background Multisite implementation research in justice and health settings often does not systematically assess differential degrees of project involvement among participating sites, despite its implications for both research and the intervention. Tracking organization and participant involvement across sites, when attempted, has typically entailed the use of discrete and sometimes disjointed fidelity measures that may not accurately reflect engagement with a project. This article advances a more comprehensive and sophisticated conceptual model for measuring and monitoring site engagement. This conceptual model was developed from a literature review of the implementation science and related disciplines while being informed by multisite project implementation experience. We propose the Site Engagement Activity Model Leveraging Implementation Science (SEAMLIS), a conceptual model that holistically identifies the breadth of agency participation (diverse activities such as trainings, meetings, etc.) and duration of site engagement (participation levels from inception to completion) to be measured, assessed, and reported. Case presentation We also describe Juvenile Justice Translational Research on Interventions for Adolescents in the Legal System (JJ-TRIALS), a 36-site implementation research project, as an illustrative case example of our proposed model. We then operationalize all proposed domains and subdomains and specify key measures from the project. Conclusions We provide analytical recommendations for the application and future research of the proposed model in health and justice settings. In multisite implementation research, site engagement could be fruitfully used as an independent, dependent, or intervening (moderating or mediating) variable. Trial registration NCT02672150, February 3, 2016.